2002
DOI: 10.1177/107155760200900104
|View full text |Cite
|
Sign up to set email alerts
|

Production of Oxytocin Receptor and Cytokines in Primary Uterine Smooth Muscle Cells Cultivated Under Inflammatory Conditions

Abstract: The constitutive and cytokine-inducible expression of interleukins from uterine smooth muscle cells suggests that the myometrium may contribute to the overall production of inflammatory mediators in the uterus that are thought to govern term- or infection-induced preterm labor. Down-regulation of the oxytocin receptor under IL-1beta in myometrial cells may indicate that initiation and maintenance of labor could be partially limited under severe inflammatory conditions such as chorioamnionitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 30 publications
(2 reference statements)
1
19
0
Order By: Relevance
“…However, hypoxia reduced the myometrial contractile response to oxytocin as well as the number of oxytocin-binding sites in the pregnant rat uterus [46][47][48]. Additionally, it was reported that hypoxia did not influence the expression of OTR mRNA in cultured human uterine smooth muscle cells [42]. Nicotine has the ability to induce arterial smooth muscle contraction, tracheal smooth muscle contraction, and gastrointestinal smooth muscle contraction, which in turn may increase the uterine smooth muscle contractile response to oxytocin.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, hypoxia reduced the myometrial contractile response to oxytocin as well as the number of oxytocin-binding sites in the pregnant rat uterus [46][47][48]. Additionally, it was reported that hypoxia did not influence the expression of OTR mRNA in cultured human uterine smooth muscle cells [42]. Nicotine has the ability to induce arterial smooth muscle contraction, tracheal smooth muscle contraction, and gastrointestinal smooth muscle contraction, which in turn may increase the uterine smooth muscle contractile response to oxytocin.…”
Section: Discussionmentioning
confidence: 97%
“…In the human adrenal gland, however, glucocorticoids inhibit 17␣-hydroxylase activity, which is involved in dehydroepiandrosterone sulfate production [39]. Interleukin-1␤ (inflammatory cytokine) and oxytocin itself each reduced the OTR mRNA level in human myometrial cells and tissues [40][41][42][43][44]. Interleukin-6 had various effects on the expression of OTR mRNA.…”
Section: Discussionmentioning
confidence: 97%
“…The oxytocin-signaling pathway may play an important role in the control of parturition, and its abnormal regulation may be implicated in preterm labor [45]. There have been conflicting reports as to whether oxytocin receptor gene expression is increased, decreased, or not changed following treatment of myometrial cells with IL1B and IL6 [30,31,46,47]. Thus, it is not clear how MAFF may be implicated in the control of the oxytocin pathway by cytokines.…”
Section: Discussionmentioning
confidence: 98%
“…However, we cannot rule out the possibility that prostaglandin synthesis during the 24-h treatment phase may have led directly, or indirectly, to permanent alterations in protein expression or Ca 2ϩ signaling. Similarly, IL-1␤ effects on Ca 2ϩ mobilization could be modulated via stimulation of production of other cytokines (e.g., IL-8) [44].…”
Section: Il-1␤ Mediated Effects On Gene Expressionmentioning
confidence: 99%